An Investigation into A Socio-Economic Fit Between Vehicular Emissions and Economic Activities: A Case Study of Commercial Vehicles - Gul, Naveed; Nazir, Naila (iRASD Journal of Economics, 2023)
Vehicular emission is one of the challenges in managing environmental pollution. The present study is designed to find a socio-economic fit between economic activities and the resultant emissions associated with automobiles. To proceed, it focuses on estimating seven different types of vehicular emissions; carbon monoxide, carbon dioxide, nitrogen oxide, particulate matter 2.5 and 10, volatile organic compounds, and the total suspended particulate matter. This exercise is based on data from a sample of 1200 respondents from the district of Peshawar. Results demonstrate that socio-economic factors and vehicle-specific characteristics significantly affect the excessive vehicular emission in the study area. It has been found that the socio-economic variables like age of respondent, education of respondents, and family size of the respondent, earning members in respondent’s family, monthly income of the respondents, total household expenditures, and wealth are factors significantly affecting commercial automobiles' emissions. Moreover, it was found that the cost incurred on the maintenance of the vehicle by the owner/driver is within the income range of the respondent. Based on the results, it is recommended that the identification and countering of challenges being raised by the emissions from commercial automobiles is very important for both the environment and the economy. This can only be done by a comprehensive cost-benefit analysis among different but conflicting priorities. As a top priority, the Khyber Pakhtunkhwa Government Driving School may be revamped to impart more efficient and effective training on road awareness and the resultant emissions from automobiles. Similarly, the Khyber Pakhtunkhwa Vehicle Emissions Testing Station (VETS) should be upgraded with the latest as well as smart machinery and equipment, especially the mobile testing stations that operate in shifts to cover the round-the-clock monitoring. Also, the emission fitness certificate shall be made conditional for the annual tax token renewals. The replacement of old and outdated engines with modern Euro–VI engines shall be incentivized so that the drivers are encouraged for the shift, ultimately benefiting both the environment and the drivers economically.